Climate information services need for livestock production in Senegal and priorities for investment - Ouédraogo, Issa; Ramírez Villegas, Julián Armando; Banerjee, Rupsha R. (CGIAR Initiative on Livestock and Climate, 2022)
Climate change and variability is affecting the livestock production system in Senegal. The use of relevant climate information services (CIS) in the livestock production value chain has the potential to build the resilience and productivity of transhumant pastoralists. The demand for CIS has increased today at a stage where several pastoral communities are willing to contribute to the cost of CIS production. Attempts to promote and scale up access to and use of CIS have been successful for the farming and fishing sectors in Senegal but this has not been the case for the livestock sector due to various reasons including failure to produce needed CIS and to set up dedicated CIS dissemination channels. The ONECGIAR Initiative on Livestock and Climate (LAC), under its work package 2 is taking stock of achievements from previous projects to deliver salient CIS to pastoral communities in the Ferlo zone of Senegal. To this end, fine-tuning the need assessment in terms of CIS (types, resolution, frequency etc.), dissemination channels and capacity building is a prerequisite. Therefore, stakeholders’ consultation meetings and a review of existing literature were used to assess the needs. In total, 15 CIS have been identified by the various stakeholders of which seven are already available; several CIS dissemination channels have been identified of which, community radio and mobile network operators’ platforms such as SMS and IVR are the most preferred ones. There is also a need to translate CIS into advisories suitable for each agroecological zone. This will require some capacity building of the multidisciplinary working groups (MWG) for each target district.